IMPLEMENTASI P5 MEDIA DIY HOME PROJECT: MENGEMBANGKAN KEMANDIRIAN SISWA PELAJARAN SENI BUDAYA - Sri Muafifah; Lutfi Fadilah; Hanif Amrulloh (Universitas Islam Lamongan, 2025)
Learning independence is a very important skill and needs to be developed, especially in art and culture lessons in elementary schools. When conducting observations, researchers found a low level of independence of students in class III C MI NU Metro when doing assignments, such as copying their friends' answers, not bringing equipment for drawing, which caused the learning process to be unconducive. So an effective learning approach is needed, namely by implementing DIY (Do It Yourself) home project media in the context of P5, namely independence. This study aims to determine the Implementation of P5 in developing student learning independence in Art and Culture lessons through DIY home projects. This study uses a qualitative approach with a case study method.